2009
DOI: 10.1088/0004-637x/698/1/324
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF STRUCTURE IN INFRARED-DARK CLOUDS WITHSPITZER: CHARACTERIZING STAR FORMATION IN THE MOLECULAR RING

Abstract: We have conducted a survey of a sample of infrared-dark clouds (IRDCs) with the Spitzer Space Telescope in order to explore their mass distribution. We present a method for tracing mass using dust absorption against the bright Galactic background at 8 μm. The IRDCs in this sample are comprised of tens of clumps, ranging in sizes from 0.02 to 0.3 pc in diameter and masses from 0.5 to a few 10 3 M , the broadest dynamic range in any clump mass spectrum study to date. Structure with this range in scales confirms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 71 publications
(166 reference statements)
6
90
2
Order By: Relevance
“…Marshall et al (2009), Ragan et al (2009), and Peretto & Fuller (2010 have studied the mass distribution of IRDCs obtained from extinction maps. In particular, Ragan et al (2009) computed the mass distribution of cores using Clumpfind in 11 IRDCs and fitted broken power laws of α low = −0.52 ± 0.04 and α high = −1.76 ± 0.05 for masses lower than 40 M and for masses greater than 40 M , (Simon et al 2006b), Pe10 (Peretto & Fuller 2010), Ma09 (Marshall et al 2009), Mi12 (Miettinen 2012), Ra09 (Ragan et al 2009), Re06a (Reid & Wilson 2006a), Mo04 (Mookerjea et al 2004), Mu07 (Muñoz et al 2007). respectively. Using Gaussclumps, the slope becomes shallower: α high = −1.15 ± 0.04 and α low = −0.64 ± 0.07 for the same break-point mass.…”
Section: Mass Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Marshall et al (2009), Ragan et al (2009), and Peretto & Fuller (2010 have studied the mass distribution of IRDCs obtained from extinction maps. In particular, Ragan et al (2009) computed the mass distribution of cores using Clumpfind in 11 IRDCs and fitted broken power laws of α low = −0.52 ± 0.04 and α high = −1.76 ± 0.05 for masses lower than 40 M and for masses greater than 40 M , (Simon et al 2006b), Pe10 (Peretto & Fuller 2010), Ma09 (Marshall et al 2009), Mi12 (Miettinen 2012), Ra09 (Ragan et al 2009), Re06a (Reid & Wilson 2006a), Mo04 (Mookerjea et al 2004), Mu07 (Muñoz et al 2007). respectively. Using Gaussclumps, the slope becomes shallower: α high = −1.15 ± 0.04 and α low = −0.64 ± 0.07 for the same break-point mass.…”
Section: Mass Spectramentioning
confidence: 99%
“…Therefore, IRDCs are good candidates for studying the mass distribution of their clumps/cores. Different studies of the mass distributions of IRDCs based on either extinction or continuum maps and different assumptions, e.g., source extraction, mass estimation, etc., find a range of indices from α ∼ −1.7 to −2.1 (e.g., Rathborne et al 2006;Ragan et al 2009;Peretto & Fuller 2010;Miettinen 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Rathborne et al 2006;Ragan et al 2009;Battersby et al 2010). They are located throughout the Galactic plane, concentrated within the spiral arms (Jackson et al 2008).…”
Section: Background and Motivationmentioning
confidence: 99%
“…Since then, follow-up Full Table 1 is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/590/A72 observations have shown that these sources are cold, dense molecular clouds and potential mass reservoirs for future generations of stars (e.g. Teyssier et al 2002;Simon et al 2006;Rathborne et al 2006;Ragan et al 2009). Their darkness in the mid-infrared domain ensures that these sources represent early stages in dense cloud evolution and, as such, IRDCs might contain the initial conditions of star formation.…”
Section: Introductionmentioning
confidence: 99%